2017
DOI: 10.2147/ijn.s114356
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo mechanism for the reduced peripheral neurotoxicity of NK105: a paclitaxel-incorporating polymeric micellar nanoparticle formulation

Abstract: In our previous rodent studies, the paclitaxel (PTX)-incorporating polymeric micellar nanoparticle formulation NK105 had showed significantly stronger antitumor effects and reduced peripheral neurotoxicity than PTX dissolved in Cremophor ® EL and ethanol (PTX/CRE). Thus, to elucidate the mechanisms underlying reduced peripheral neurotoxicity due to NK105, we performed pharmacokinetic analyses of NK105 and PTX/CRE in rats. Among neural tissues, the highest PTX concentrations were found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…NK105 significantly diminished neurotoxicity, as confirmed by both electrophysiological and morphological methods, exhibiting slightly increase in the caudal sensory nerve action potential (caudal SNAP) compared to control (i.e., glucose injection), as well as showing less incidence of degenerated myelinated nerve fibers in rats than that treated with PTX (Figure 2B,C). [ 52 ] A later in vivo study revealed that the mechanism for the reduced peripheral neurotoxicity of NK105 was the much lower concentration of PTX in the dorsal root ganglion (DRG) compared to free PTX, [ 55 ] which may be due to the large diameter of NK105 for extravasating the blood vessels of DRG.…”
Section: Self‐assembled Cancer Nanomedicines In Preclinical and Clinimentioning
confidence: 99%
“…NK105 significantly diminished neurotoxicity, as confirmed by both electrophysiological and morphological methods, exhibiting slightly increase in the caudal sensory nerve action potential (caudal SNAP) compared to control (i.e., glucose injection), as well as showing less incidence of degenerated myelinated nerve fibers in rats than that treated with PTX (Figure 2B,C). [ 52 ] A later in vivo study revealed that the mechanism for the reduced peripheral neurotoxicity of NK105 was the much lower concentration of PTX in the dorsal root ganglion (DRG) compared to free PTX, [ 55 ] which may be due to the large diameter of NK105 for extravasating the blood vessels of DRG.…”
Section: Self‐assembled Cancer Nanomedicines In Preclinical and Clinimentioning
confidence: 99%
“…Therefore, some PTXloaded nanoparticle formulations have been developed and applied into clinic such as albumin-entrapped PTX (Abraxane™) and the polymeric micelle formulation (NK105 and Genexol-PM™). 18,19 The in vivo PK/PD models of PTX (including PTX-loaded nanoparticles) have been developed to relate the pharmacokinetics to the toxicity effect 2,20 or the magnitude of the pharmacologic effect. However, in vitro PK/PD models are rare studied and may be of great value, as it may facilitate the individualized chemotherapy of nanomedicine with the in vivo model.…”
Section: Introductionmentioning
confidence: 99%
“…Among these formulations, polymeric micelles have been proven as promising drug delivery systems for PTX administration [ 9 , 10 ], because of their attractive characteristics, such as biocompatibility, high drug-loading content, small size (<200 nm) and propensity to evade scavenging by the mononuclear phagocyte system (MPS) [ 11 , 12 ]. Moreover, the nanoscale dimensions of polymeric micelles permit their selectively accumulation in tumor tissues due to the enhanced permeability and retention (EPR) effect, which is termed “passive targeting” [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%